Profiling of sugar transporter genes in grapevine coping with water deficit. Issue 21 (26th September 2014) - Medici, Anna; Laloi, Maryse; Atanassova, Rossitza
Abstract : The profiling of grapevine ( Vitis vinifera L.) genes under water deficit was specifically targeted to sugar transporters. Leaf water status was characterized by physiological parameters and soluble sugars content. The expression analysis provided evidence that VvHT1 hexose transporter gene was strongly down‐regulated by the increased sugar content under mild water‐deficit. The genes of monosaccharide transporter VvHT5, sucrose carrier VvSUC11, vacuolar invertase VvGIN2 and grape ASR (ABA, stress, ripening) were up‐regulated under severe water stress. Their regulation in a drought‐ABA signalling network and possible roles in complex interdependence between sugar subcellular partitioning and cell influx/efflux under Grapevine acclimation to dehydration are discussed. Abstract : Profiling of sugar transporter genes in grapevine leaves under water‐deficit and during recovery. VvHT1 gene is strongly down‐regulated by the increased sugar content early under mild water deficit. VvHT5, VvSUC11 and VvGIN2 genes are highly up‐regulated upon severe water stress. Grape ASR gene is a water‐stress marker and a possible key factor allowing the plant to cope with drought. Studied genes seem transcriptionally regulated in a complex drought‐ and ABA‐signalling network.